Interfacial modification layers based on carbon dots for efficient inverted polymer solar cells exceeding 10% power conversion efficiency. (August 2016) - Lin, Xiaofeng; Yang, Yuzhao; Nian, Li; Su, Hua; Ou, Jiemei; Yuan, Zhongke; Xie, Fangyan; Hong, Wei; Yu, Dingshan; Zhang, Mingqiu; Ma, Yuguang; Chen, Xudong
Abstract: Herein, we have demonstrated that rationally-designed carbon dots (C-dots) with amino groups, for the first time, were used as an efficient interfacial modification layer on the ZnO or AZO interlayers, greatly improving the device performance. The C-dots modifying showed decreased work function and smoothed surface of metal oxides, facilitating the enhancement of charge extraction efficiency and the decrease of recombination losses for the cathode. More importantly, the C-dots showed the luminescent down-shifting effect, beneficial for the increase of the light conversion for near ultraviolet and blue-violet portions of sunlight. As a result, by incorporating ZnO/C-dots as the interlayers, our designed inverted polymer solar cells with PTB7:PC71 BM as the active layer obtained over 20% enhancement compared with the devices with pure ZnO (from 7.41% to 9.01%). Notably, a maximum PCE of up to 10.24% was achieved with the AZO/C-dots as the interlayers and PTB7-Th:PC71 BM instead of PTB7:PC71 BM as the active layer, and this efficiency outperforms all previously reported PSCs using carbon materials as additives in the active layer or the interface materials. Our PCE value is also higher than those of many previously reported bulk-heterojunction (BHJ) solar cells using the organic polymer modifier. Graphical abstract: Highlights: Reported C-dots with amino groups as an interfacial modification layer for the first time. The C-dots modification can result in decreased work function and smoothed surface of the metal oxides and thus enhance charge extraction efficiency for the cathode. The luminescent down-shifting effect of C-dots can increases the utilization of near ultraviolet and blue-violet portions of sunlight. The optimized device based on PTB7-Th:PC71 BM achieves a maximum PCE of up to 10.24%, outperforming previously reported PSCs using carbon nano-materials as additives so far.